Photosensitivity n-channel ZnO phototransistor for optoelectronic applications: Modeling of ZnO TFT - Yakuphanoğlu, Fahrettin; Mansouri, S. (Pergamon-Elsevier Science Ltd, 2011)
The zinc oxide semiconductor thin film transistor was fabricated on a SiO2/Si substrate by sol gel method. The ZnO film is consisted of nanofibers with the changing diameter along the fibers. Electrical characteristics of the zinc oxide transistor under dark and white light illuminations were analyzed. The mobility value of the ZnO TFT was found to be 1.86 x 10(-2) cm(2)/V s. The ZnO thin film transistor works in an n-channel operational mode because the drain current increases with the positive gate voltages. A significant increase in the drain current of ZnO TFT is observed with a maximum photosensitivity of 100 under visible light illumination. It is concluded that the ZnO thin film transistor can be used in visible photo-detecting device applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Thin-Film Transistors; Semiconductor; Fabrication